Here, there and everywhere. (Economist, 2000)
New software that makes it possible for Internet users to exchange files also makes it more difficult for those worried about copyright and censorship to prevent this. A new form of “distributed” systems for storing and gathering information has been developed that has the potential to change the Internet more than any other phenomenon since the creation of web browsers. Personal computers have enough power and storage space to act as servers, which can be hooked together and into the Internet to form huge storage networks. The main problem associated with such systems is that they cannot be searched by users. However, new technology is being developed that will lead to new applications, including real-time searching. The storages networks could be used as a means of spreading content across the Internet, or to aid in the preservation of digital content. These networks will also have regulatory and economic implications, especially in relation to the control of online content. They will also influence telecommunications and computer industries.